Analysis of Factors Affecting GRDP per Capita in Eastern Indonesia: A Panel and Spatial Model Approach in the Context of the Planned Capital Relocation (IKN) - Andi Aulia Khairunnisa; Fani Rahmasari (Publication of the International Journal and Academic Research, 2025)
The Gross Regional Domestic Product (GRDP) per capita in Eastern Indonesia, particularly in provinces adjacent to the planned new capital city (IKN), is influenced by various economic and infrastructural factors. This study examines the impact of national road length, population density, foreign investment, the Human Development Index (HDI), and poverty levels on economic growth in the region. Using data from multiple provinces, the analysis employs panel data models (Pooled OLS, Fixed Effect, and Random Effect), spatial models (Spatial Durbin Model), and autoregressive tests to observe temporal relationships. The entire analysis is conducted using RStudio, allowing for efficient data processing and advanced econometric modeling. The findings indicate that infrastructure development (measured by national road length), population (in total population), and quality of life (measured by Human Development Index/HDI) have a statistically significant effect on GRDP per capita in Eastern Indonesia. Meanwhile, foreign direct investment (FDI) shows no significant influence in the model. Therefore, economic policies that incorporate spatial and temporal considerations especially those targeting infrastructure, demographic dynamics, and human development are crucial for fostering more equitable and sustainable growth across Eastern Indonesia.